Modified In-Office Maxillary Balloon Sinus Dilation for Post-Procedure Sinus Monitoring and Access - Nishioka,Gary J. (2018)
Abstract Introduction As experience grows with in-office balloon sinus dilation (BSD) procedures, technique modifications will evolve to meet specific needs. The major disadvantage with the maxillary BSD procedure is that the intact uncinate process prevents visualization of and instrument access into the maxillary sinus both intraoperatively and postoperatively. Combining a partial or complete uncinectomy procedure with maxillary BSD could be beneficial in selected patients with certain maxillary sinus problems. Objective The primary objective of this study was to see if, in selected patients, combining an uncinectomy and maxillary sinus BSD together allowed visualization of and access to the maxillary sinus cavity at the time of the procedure and at follow-up visits. Method A chart review was completed for BSD cases performed from 2013 through mid-2015 identifying patients who underwent partial or complete uncinectomy with in-office maxillary sinus BSD. A total of 14 patients were identified, with 26 sinuses treated. The data collected included: difficulty or problems in performing an uncinectomy with the maxillary sinus BSD; visualization and access to the maxillary sinus cavity both intraoperatively and at follow-up visits; and occurrence of complications or late adverse sequelae. All patients completed a minimum 6-month follow-up. Results Combined uncinectomy and maxillary sinus BSD procedures were easily completed for all patients without complications, and no late adverse sequelae were encountered. The maxillary sinuses could be visualized and accessed, if needed, intraoperatively and at all follow-up visits. Conclusions In selected subsets of maxillary sinus conditions this procedure modification can provide significant benefits. A case is presented for illustration.